Functional MRI Correlates of Carbon Dioxide Chemosensing in Persons With Epilepsy - Hampson, Johnson P.; Lacuey, Nuria; Rani, MR Sandhya; Hampson, Jaison S.; Simeone, Kristina A.; Simeone, Timothy A.; Narayana, Ponnada A.; Lemieux, Louis; Lhatoo, Samden D. (Frontiers in Neurology, 2022)
Objectives: Sudden Unexpected Death in Epilepsy (SUDEP) is a catastrophic epilepsy outcome for which there are no reliable premortem imaging biomarkers of risk. Pericital respiratory depression is seen in monitored SUDEP and near SUDEP cases, and abnormal chemosensing of raised blood carbon dioxide (CO2) is thought to contribute. Damage to brainstem respiratory control and chemosensing structures has been demonstrated in structural imaging and neuropathological studies of SUDEP. We hypothesized that functional MRI (fMRI) correlates of abnormal chemosensing are detectable in brainstems ofpersons with epilepsy (PWE) andare different from healthy controls (HC). . Methods: We analyzed fMRI BOLD activation and brain connectivity in ten PWE and ten age-sex matched HC during precisely metered iso-oxic, hypercapnic breathing challenges. Segmented brainstem responses were of particular interest, along with characterization of functional connectivity metrics between these structures. Regional BOLD activations during hypercapnic challenges were convolved with hemodynamic responses, and the resulting activation maps were passed on to group-level analyses. For the functional connectivity analysis, significant clusters from BOLD results were used as seeds. Each individual seed time-series activation map was extracted for bivariate correlation coefficient analyses to study changes in brain connectivity between PWE and HCs. Results: (1) Greater brainstem BOLD activations in PWE compared to HC during hypercapnic challenges in several structures with respiratory/chemosensing properties. Group comparison between PWE vs. HC showed significantly greater activation in the dorsal raphe among PWE (P<0.05) compared to HCs. (2) PWE had significantly greater seed-seed connectivity and recruited more structures during hypercapnia compared to HC. Significance: The results of this study show that BOLD responses to hypercapnia in human brainstems are detectable and different in PWE compared to HC. Increased dorsal raphe BOLD activation in PWE, and increased seed-seed connectivity between brainstem and adjacent subcortical areas, may indicate abnormal chemosensing in these individuals. Imaging investigation of brainstem respiratory centers involved in respiratory regulation in PWE is an important step towards identifying suspected dysfunction of brainstem breathing control that culminates in SUDEP and are deserving of further study as potential imaging SUDEP biomarkers